Evaluating Electronic Learning Reality in Fencing Class in Physical Education and Sport Sciences from Students Point of View - Abdul Khalik, Sajad Abdul Wahid (Journal of Physical Education, 2021)
The study aimed at designing a questionnaire for evaluating e-learning reality in fencing class as well as identifying the evaluation of e-learning from the students’ point of view. The researcher used the descriptive method on (170) students who attend electronic fencing classes from the third-year college of physical education and sport sciences students. The subjects were divided into three groups and the researcher designed a questionnaire using google drive after applying it in a pilot study on (5) students. The data was collected and treated using SPSS to conclude that e classes support academic knowledge in fencing class from the students’ point of view but it decreases the students’ active participation in class. Fencing class requires continuous correction from the teacher a matter that negatively affected learning as well as the fencing class requires a teaching program that suits the equipment used in the practical lesson a matter that cannot be provided outside of sport halls. The researcher recommended developing a fencing classes with suitable electronic programs for fencing to increase the students’ role. He finally recommended providing material appropriate to electronic learning that can be used during emergencies such as Covid -19.